Non-Tariff Measures Impact on Indonesian Fishery Export - Permata, Sonia Puspa; Handoyo, Rossanto Dwi (Journal of Developing Economies, 2019)
This study aims to analyze the impact of Non tariff measures using sanitary and phytosanitary policy (SPS) and technical trade barriers (TBTs) on fishery exports of Indonesia and its trading partner countries such as China, South Korea, Vietnam, Canada, Russia and the European Union in period of 2007 to 2016. SPS and TBT are measured using inventory approach in the form of coverage ratio. In addition, this study uses a gravity model and panel data regression method. The results of this study indicate that the variables GDP of exporting country and GDP of importing country have a positive and significant effect on Indonesian fishery exports. Distance and SPS have a negative and significant effect on Indonesian fishery exports, while TBT has no effect on Indonesian fishery exports.   Keywords: Export, SPS and TBT, Fishery Export, Coverage Ratio JEL Classification: F10, F130